Factors That Impact Measures of Grit among Nursing Students: A Journey Emblematic of the Koi Fish - Daniel Terry; Blake Peck (MDPI AG, 2020)
Grit is the capacity to persevere, to have passion, and be committed to achieve goals long-term regardless of adversity or challenge. Grit provides an insight into why some nursing students succeed academically or clinically, while others do not. This quantitative cross-sectional correlational study measured levels of grit among nursing students undertaking a three-year bachelor's degree program. All students (n = 2349) within the program were invited to complete a questionnaire which included the short grit scale (Grit-S) which measured each student's level of perseverance and passion. Overall, it was highlighted that increased levels of grit correlated with an increase in the student's year of study, greater perceived clinical and academic performance, not using television as a motivator for entry to nursing, being lower on the socio-economic spectrum, and being older in age. Grit was found to develop exponentially as students entered second and third years, suggesting that a balance of constant academic and clinical challenge was an impetus for many to achieve in the face of adversity, and is reminiscent of the journey of the koi fish. This paper culminates in a call for educators to consider the inclusion of creative grit forming challenges that focus on developing a student's sense of open-mindedness within first year of undergraduate nursing programs.